Application of time-domain reflectometry to determine the thickness of the frozen zone in soils - Baker, T. H. W.; Davis, J. L. (1982)
Time-domain reflectometry is an electromagnetic pulse technique that has been used to measure the dielectric constant of soils at frequencies between 1MHz and 1GHz. The dielectric constant of water is 30 times that of ice, making it possible to delineate the freezing front in soils. Results of laboratory experiments will be presented to show the application of this technique to determine the thickness of the frozen zone in coarse-grained and fine-grained soils. The location of the freezing boundary using time- domain reflectometry will be compared with temperature measurements and interpretations from X-ray photographs. La réflectométrie associée au temps est une technique faisant intervenir des impulsions électromagnétiques qui a été utilisée pour mesurer la constante diélectrique des sols à des fréquences variant entre 1 MHz et 1 GHz. La constante diélectrique de l'eau équivaut à 30 fois celle de la glace, ce qui fait qu'il est possible de situer le front de congélation dans les sols. Les résultats d'expériences en laboratoire sont présentés afin d'illustrer l'application de cette technique à la mesure de l'épaisseur de la zone gelée de sols à granulométrie grossière et fine. L'emplacement de la limite de congélation située à l'aide de la réflectométrie associé au temps est comparé aux résultats obtenus par des mesures de la température et par l'interprétation de photographies aux rayons-X. Peer reviewed: Yes NRC publication: Yes